Elevated Temperature Reduces Overwintering Survival of an Avian Ectoparasite, the Swallow Bug (Hemiptera: Cimicidae: Cimex vicarius). Issue 2 (28th March 2022) - Brown, Charles R; Hannebaum, Stacey L; Eaton-Clark, Andrew; Booth, Warren; O'Brien, Valerie A
Abstract: The survival of insects that are dormant in winter may either increase or decrease as a consequence of elevated winter temperatures under climate change. Warming can be deleterious when metabolism of the overwintering life stages increases to the point that energy reserves are exhausted before postoverwintering reemergence. We examined experimentally how overwintering survival of swallow bugs (Hemiptera: Cimicidae: Cimex vicarius Horvath), an ectoparasite primarily of cliff swallows (Passeriformes: Hirundinidae: Petrochelidon pyrrhonota Vieillot), was affected by a 3°C rise in mean daily temperature for populations in Oklahoma, Nebraska, and North Dakota. Adult and nymphal swallow bugs exposed to elevated temperature had an average reduction of approximately 31% in overwintering survival (from July/August to April/May), relative to controls exposed to current region-specific ambient-like conditions. Adult males in both groups survived less well in Nebraska and North Dakota than adult males in Oklahoma, but there was no consistent latitudinal effect of the elevated heat treatment. Our results indicate that projected increases in mean temperature in the Great Plains by 2050 could result in fewer swallow bugs surviving the winter and thus a reduced population size upon the arrival of their primary host in the spring, potentially affecting cliff swallow reproductive success, site use, and breeding phenology. Global climate change may alter the dynamics of host–parasite systems by reducing overall parasite abundance.